CREATIVITY IN THE CONTEMPORARY RUSSIAN LANGUAGE VOCABULARY: “WORD OF THE YEAR” - Melnik, Uluia Aleksandrovna; Kirova, Anastasia Vladimirovna (Neofilologiâ, 2018)
The neologization with the popularity of the Internet occurs actively in the contemporary Russian language. Not only mass media but also common people, Internet users contribute significantly. New words from the media discourse get into word creating rates of Internet project “Word of the Year”. On the one hand, ranked lists are the indicators of social changes, on the other hand, they reflect linguocreative potential of people, who participate in lists formation. Creative speech activity relates to language game. One of the main rules of such a game is the understanding of conditions of a certain speech (game) code both by a creator of a word and by an interlocutor. Conducted analysis shows that authors mostly use the model of compressive word creation and it proves high creative potential, freedom of speech behavior and linguistic sense of native speakers, who strive to the self-expression with word creation. New formations created by methods of paronymic attraction and blend words save semantic links with original words. So they have semantic of motivating words in their meaning and have advantage over descriptive constructions. Thus, methods of word creation, which allow describing social and political events of a country or a personal life with a new bright word with evaluative element in it, are popular in the contemporary word creative activity.